2014
DOI: 10.1155/2014/239706
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis System for Hepatocellular Carcinoma Based on Fractal Dimension of Morphometric Elements Integrated in an Artificial Neural Network

Abstract: Background and Aims. Hepatocellular carcinoma (HCC) remains a leading cause of death by cancer worldwide. Computerized diagnosis systems relying on novel imaging markers gained significant importance in recent years. Our aim was to integrate a novel morphometric measurement—the fractal dimension (FD)—into an artificial neural network (ANN) designed to diagnose HCC. Material and Methods. The study included 21 HCC and 28 liver metastases (LM) patients scheduled for surgery. We performed hematoxylin staining for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 34 publications
0
18
4
Order By: Relevance
“…Fractal texture analysis provides information beyond what is visible at a simple inspection, without the need of additional images [ 26 , 27 ]. Our study, even if carried out on a relatively small number of patients, keeps statistical significance due to the large number of images used for each studied group.…”
Section: Discussionmentioning
confidence: 99%
“…Fractal texture analysis provides information beyond what is visible at a simple inspection, without the need of additional images [ 26 , 27 ]. Our study, even if carried out on a relatively small number of patients, keeps statistical significance due to the large number of images used for each studied group.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies concluded that fractal dimension can be implemented as prognostic factor for many carcinomas and successfully applied when analysing response to chemotherapy [13]. Fractal and stereological analysis helps us to gain a better understanding of the morphological changes in the exocrine pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that computerised analysis of microscopic images is an objective and reproducible method for diagnostic and prognostic purposes [1,6,12,13]. Fractal analysis allows for the detection of subtle morphologic changes.…”
Section: Introductionmentioning
confidence: 99%
“…Also some studies also theorized on the usage of FD in cancer prognosis (25,26). Gheonea et al reported that nuclear and vascular FDs calculated from histological images are good quantifiers for morphological aspects of liver parenchyma and can therefore fit perfectly as input variables in a perceptron feed-forward hiddenlayer ANN system (27). Epigallactocathechin has been proposed to possess various properties including the ability to induce anti angiogenesis, apoptosis, cell cycle regulation, and antimicrobial activity (28).…”
Section: Discussionmentioning
confidence: 99%